Neuroinflammation Involved in Diabetes-Related Pain and Itch - Fang, Xiao-Xia; Wang, Heng; Song, Hao-Lin; Wang, Juan; Zhang, Zhi-Jun (Frontiers in Pharmacology, 2022)
Diabetes mellitus (DM) is a global epidemic with increasing incidence, which results in diverse complications, seriously affects the patient quality of life, and brings huge economic burdens to the society. Diabetic neuropathy is the most common chronic complications of DM, resulting in neuropathic pain and chronic itch. The precise mechanisms of diabetic neuropathy have not been fully clarified, hindering to the exploration of novel therapies for diabetic neuropathy and its terrible symptoms such as diabetic pain and itch. Accumulating evidence suggests that neuroinflammation plays a critical role in the pathophysiologic process of neuropathic pain and chronic itch. Indeed, researchers have currently made significant progress in knowing the role of glial cells and the pro-inflammatory mediators produced from glial cells in the modulation of chronic pain and itch signal processing. Here, we provide an overview of current understanding of neuroinflammation in contributing to sensitization of the peripheral nervous system (PNS) and central nervous system (CNS). In addition, we also summarize the inflammation mechanisms contribute to pathogenesis of diabetic itch, including activation of glial cells, oxidative stress, pro-inflammatory factors. Targeting excessive neuroinflammation may provide potential and effective therapies for treatment of chronic neuropathic pain and itch in DM.